La revolución de septiembre y el "Diario de Reus" / Salvador Aragonés Vidal; prólogo de José María Fontana Tarrats - Fontana, José María (1911-1982); Aragonés Vidal, Salvador (Ediciones "Rosa de Reus"; v. 43)
Tirada de 500 ejemp.